Correlates of unmet needs and psychological distress in adolescent and young adults who have a parent diagnosed with cancer. Issue 4 (17th August 2015) - McDonald, F. E. J.; Patterson, P.; White, K. J.; Butow, P. N.; Costa, D. S. J.; Kerridge, I.
Abstract: Objective: Young people who have a parent with cancer experience elevated levels of psychological distress and unmet needs. In this study, we examined the associations between demographics, cancer variables and family functioning and levels of distress and unmet needs amongst young people who have a parent diagnosed with cancer. Methods: Young people aged 12–24 years with a parent with cancer ( n  = 255) completed the Offspring Cancer Needs Instrument (unmet needs), the Kessler‐10 (distress) and the Family Relationship Index (family functioning), along with measures of demographics and cancer variables (such as age, sex and time since cancer diagnosis). Variables associated with distress and unmet needs (including unmet need domains) were assessed using multiple linear regression. Results: Being female and older, having more unmet cancer needs and poorer family functioning were associated with increased distress. Having a father with cancer, a shorter time since diagnosis and poor family functioning were associated with increased unmet needs. Family conflict and expressiveness were particularly important components of family functioning. Having a parent relapse with cancer was also associated with unmet needs in the domains of practical assistance, 'time out' and support from other young people who have been through something similar. Conclusions: Delineating factors associated with increased distress and unmet needs assist in identifying at‐risk young people allowing improved assessment and tailoring of support to improve the psychosocial outcomes of young people impacted by parental cancer. Copyright © 2015 John Wiley & Sons, Ltd.